Strategi pemasaran perbankan syariah di era digital: sinergi nilai islam, bauran pemasaran, dan inovasi teknologi - Farika, Alya (Maliki Interdisciplinary Journal, 2025)
This study discusses the management of Islamic banking marketing strategies today, emphasizing the integration of Islamic values, the application of the Islamic marketing mix, and the use of information technology. The research method used is a qualitative literature review based on a review of various literature related to Islamic marketing and banking digitalization. The results show that an effective marketing strategy must be based on the principles of justice, transparency, and blessings, and implemented through nine elements of the Islamic marketing mix that are oriented towards ethics and service. Digital transformation is a crucial factor in expanding market reach and increasing customer loyalty, although its success is greatly influenced by digital literacy and the institution’s consistency in providing Islamic value-based education.